رفـع الأداء العـام في المؤسسات بالمعرفة وأنظمة المعلومات لتحقيق الميزة التنافسية - علالي, مخطار; ناصري, نفيسة (جامعة الوادي - University of Eloued, 2022)
تعيش المؤسسات الاقتصادية اليوم تحولات عميقة في ظل المنافسة القوية للتحكم في الاسواق حسب الخدمات او المنتجات المقدمة من طرفها ، حيث أن المنافسة لم تبق تقليدية بحسب نوع المنتوج بل اصبحت منافسة في عالم المعرفة و المعلومات وكيفية تسييرها، ذلك لأن المعلومة تبلورها المؤسسات الاقتصادية في وحداتها الى خلق معارف جيدة تخلصها من ميزات المنافس وتعطيها مراكز في الاسواق بناءا على تلك المعلومات سواء تعلقت برغبات وحاجات الزبائن لتحقيق المنافع أو للتغلغل في الاسواق ،أو لإبعاد المنافس ومفاجأته بجديد المنتجات أو الخدمات ، لتحسين مكانتها والتحكم في الاسواق و رفع الآداء وتحقيق الريادة. Long live economie institution today; deep transformation in light of the strong comptition to control the markets According to the services or products offered by it As the competition did not remain traditional according to the type of product ; but rather became a competition in the world of knowledge and information and how to manage it ; because the information crystallized by the economic institutions in their units to create good knowledge that rids them of the advantages of competitors ; it give them positions in the markets based on that information ; whether it is related to the desires and needs of customers to achieve benefits or to penetrate the markets ; or to keep the competitor away and surprise him with new products or service; to improve its position ; control the markets ; raise performance and acheieve leadership .
Raising the general performance in institutions with knowledge and information systems to achieve competitive advantage
مقال
Keywords: الآداء- المعرفة- المعلومة- المؤسسات، كوفيد-19; Performance ; knowledge ;information ; institution ; Covid-19 .